The adventures of ulysses - Claybourne, Anna; Anderson, Jeff Homer (Usborne London, 2002)
A fast-moving retelling of the classic story of Ulysses. Designed for children from around the age of nine, it is part of the Usborne Classics range, which covers a variety of authors and periods, and seeks to introduce the younger reader to the great works and authors of literature